Organic Solid Waste: A Scientometric Analysis on the Use of Composting for Fertilizer Generation (Research, Society and Development, 2018)
Composting consists of transforming the organic matter into compost used as fertilizer, returning the nutrients to the soil. This research aimed to analyze the space-time evolution of the publication of articles that discuss the use of composting for fertilizer production. A total of 467 articles were obtained using keywords in the Web of Science database published between 1992 and 2017. There was an increase in the number of publications from 2010. The most published countries were Spain, followed by Italy and the United States. The journals with the largest number of articles were Environmental Sciences and Soil Science; already the most cited research areas were Agriculture and Ecology of Environmental Sciences. The most frequently mentioned macronutrients were nitrogen, phosphorus and potassium; already among the micronutrients can be emphasized zinc and copper. Cultures were cited in 47.5% of the analyzed articles, with corn, tomato and wheat being highlighted. The number of publications has increased over the years, showing the search for sustainable alternatives such as composting that produces nutrient-rich compounds and organic matter.